Answer:
![x = (-41)/(17) , y = (-1)/(17)](https://img.qammunity.org/2021/formulas/mathematics/college/mkyxwvmv0igir9tlm9i8vjha8kjh1ekrrp.png)
Explanation:
Step(i):-
Given equations are 2 x+3 y=-5 ...(i)
5 x-y=-12 ...(ii)
Multiply equation (ii) by '3'
2 x + 3 y = -5
15 x - 3 y = - 36
17 x = - 41
![x = (-41)/(17)](https://img.qammunity.org/2021/formulas/mathematics/college/b42dk73cptlz5l068wtwql98hqs9vwneij.png)
Step(ii):-
Substitute
in equation (i)
2 (
+3 y=-5
3 y = - 5 +
![(82)/(17)](https://img.qammunity.org/2021/formulas/mathematics/college/yg35m1hu6knpst11ygkwxjf8dcli10bxfc.png)
![3 y = (-85 + 82)/(17) = (-3)/(17)](https://img.qammunity.org/2021/formulas/mathematics/college/v3e48no5q8labog5plhgpl46b0trkamxks.png)
![y = (-1)/(17)](https://img.qammunity.org/2021/formulas/mathematics/college/4f1dopbqpz3e11jt7t2iq05m5o4llqxwda.png)
The solution of the two equations
( x, y ) =
![((-41)/(17) , (-1)/(17))](https://img.qammunity.org/2021/formulas/mathematics/college/a8w06b31rtcd1yofesh4o5qdpvd6m1ejy7.png)